2022
DOI: 10.1016/j.avsg.2022.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Tailored Approach for Diagnostics and Treatment of Mycotic Abdominal Aortic Aneurysm

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In studies of mycotic aneurysms roughly half of patients are found to have a fusiform aneurysm, not a pseudoaneurysm or saccular aneurysm suggesting that the aneurysm was present prior to the infection. [6][7][8] The other half are found to have a pseudoaneurysm or group of pseudoaneurysms which is consistent with infection of a previously nonaneurysmal aorta. In our series, patients were ill, and it would be difficult to imagine non-operative management until an aneurysm developed.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In studies of mycotic aneurysms roughly half of patients are found to have a fusiform aneurysm, not a pseudoaneurysm or saccular aneurysm suggesting that the aneurysm was present prior to the infection. [6][7][8] The other half are found to have a pseudoaneurysm or group of pseudoaneurysms which is consistent with infection of a previously nonaneurysmal aorta. In our series, patients were ill, and it would be difficult to imagine non-operative management until an aneurysm developed.…”
Section: Discussionmentioning
confidence: 69%
“…Mycotic aneurysms are thought to arise from bacterial seeding of the aortic wall by hematogenous spread or direct communication. 6 This infectious process progresses to pseudoaneurysm or a series of pseudoaneurysms. Infection of existing aortic aneurysms, however, is also known to occur by similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 In the absence of consensus guidelines, and since there are significant variations in patient characteristics, diagnostic approaches and surgical and antibiotic treatment options, as this case highlights, a multidisciplinary and patient tailored approach including vascular surgeons, clinical microbiologists, and infectious disease experts is key to ensure the best management of patients with mycotic aortic aneurysms. 10 …”
Section: Discussionmentioning
confidence: 99%
“…39 An aneurysm may form in any part of the aorta but most commonly affects the descending thoracic aorta. 40 The rapid dilation and increased risk of rupture carry a poor prognosis and high 39,41 Patient presentations are largely nonspecific, with the most common symptoms being fever and chest pain. 39 In addition, pulmonary artery mycotic aneurysms may manifest with cough, dyspnea, and hemoptysis.…”
Section: Mycotic Aneurysmmentioning
confidence: 99%